An anatomical approach to hand rejuvenation: the AB (Anatomically Based) techniques for aesthetic injections in the hand - Garagnani, Lorenzo (Aesthetic Medicine, 2023)
Background: the focus of non-surgical rejuvenation has historically been predominantly on facial treatments, with facial anatomy being a regular training topic in aesthetic injection and aesthetic medicine courses and training programmes. Although the importance of addressing hand rejuvenation concerns has become increasingly acknowledged, the literature on this topic remains limited only to some aspects.Aim: this study aims to address the gaps in the current literature on detailed techniques for hand rejuvenation injections, describing an anatomically based approach to dermal filler and skin booster injections and addressing the specific hand changes caused by muscular wasting.Methods: the techniques described in this study are based on consolidated knowledge and widely known anatomical concepts, further confirmed by the author’s own experience as a hand and wrist surgeon and aesthetic doctor and on cadaveric hand dissections.Results: injection sites and approaches have been developed based on the anatomical features of the hand, in areas where the risk of damaging vessels, nerves, tendons, ligaments, muscles and other structures can be reduced.Conclusions: sound anatomical knowledge with awareness of the risks and potential complications allows for appropriate and safer planning and performance of aesthetic hand injections. An anatomical study based on twenty-six cadaveric hand dissections, with proposed clinical applications for hand rejuvenation is described.